"PREVALENCE, MATERNAL COMPLICATIONS AND BIRTH OUTCOME OF PHYSICAL, SEXUAL AND EMOTIONAL DOMESTIC VIOLENCE DURING PREGNANCY" - M. Faramarzi; S. Esmaelzadeh; S. Mosavi (Acta Medica Iranica, 2005)
The prevalence of physical violence during pregnancy varies widely in different societies. To assess the incidence of self-reported physical, emotional and sexual violence in pregnancy and describe the association with maternal complication and birth outcomes, 3275 women who gave birth to live-born infants from October 2002 to November 2003 were assessed for self-reported violence in postpartum units of Obstetrics Department of Babol university of Medical Sciences. Outcome data included maternal antenatal hospitalizations, labor and delivery complications and low birth weights and preterm births. Odds ratios and 95% confidence intervals were calculated to measure the association between violence, maternal morbidity and birth outcomes. The prevalence of physical, sexual and emotional domestic violence was respectively 9.1%, 30.8% and 19.2%. Compared with those not reporting physical, sexual and emotional violence, women who did were more likely to deliver by cesarean and to have abnormal progress of labor, premature rupture of membranes, low birth weight, preterm birth and any hospitalization before delivery. Prevalence of physical, emotional or sexual violence during pregnancy was high and was associated with adverse fetal and maternal conditions. These findings support routine screening for physical, emotional and sexual violence in pregnancy and postpartum period to prevent consequences of domestic violence.